A case of amyloid light amyloidosis involving multiorgan with hepatomegaly as the main manifestation - Ya-Nan CHEN; Jia-Long LIU; Yi-Zhang LI; Ji-Xia ZHANG; Xian-Yan SHI; Jing LIU (Yixue xinzhi zazhi)
Amyloid light (AL) amyloidosis, also known as primary systemic amyloidosis, is a protein conformation disease, and is a clinical syndrome of functional failure of affected organs due to abnormal folding and deposition of insoluble fibrin in the extracellular region of organs or tissues. The diagnosis of AL-type amyloidosis is challenging because of its low incidence and complex clinical manifestations, and cases of multiple organ involvement are even rarer. We reported a case of AL-type amyloidosis with multiple organ involvement in order to provide refference for related diagnosis, treatment and prognosis.